2016
DOI: 10.1002/cphc.201600602
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Fluorine‐Doped Hydrophilic Carbon Nanoparticles from Hexafluorobenzene by Femtosecond Laser Pulses

Abstract: We report on the preparation and characterization of fluorine-doped hydrophilic carbon nanoparticles by the exposure of hexafluorobenzene or a water/hexafluorobenzene bilayer solution to femtosecond laser pulses. Uniform atom distributions are achieved not only on the particle surface but also inside the particles. The semi-ionic character of C-F bonds and the non-aggregating feature of the nanoparticles play key roles in the water-dispersible character of fluorine-doped carbon nanoparticles. We suggest the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…The high‐resolution spectra of F 1s exhibit three main peaks (Figure S4d, Supporting Information): semi‐ionic CF (686.5 eV), covalent CF (687.1 eV), and CF 2 (687.8 eV) . The high amount of semi‐ionic CF bonds and amide/amino type N atoms on the surface led to the water solubility of FNCDs . Fourier‐transform infrared (FTIR) spectra of the FNCDs were also recorded, showing peaks for nitrogen in the form of CN (1635 and 1409 cm −1 ), CN (1600 cm −1 ) and amino/amide NH bonds (3310, 3188, 1534, and 736 cm −1 ) (Figure S5, Supporting Information) .…”
Section: Resultsmentioning
confidence: 99%
“…The high‐resolution spectra of F 1s exhibit three main peaks (Figure S4d, Supporting Information): semi‐ionic CF (686.5 eV), covalent CF (687.1 eV), and CF 2 (687.8 eV) . The high amount of semi‐ionic CF bonds and amide/amino type N atoms on the surface led to the water solubility of FNCDs . Fourier‐transform infrared (FTIR) spectra of the FNCDs were also recorded, showing peaks for nitrogen in the form of CN (1635 and 1409 cm −1 ), CN (1600 cm −1 ) and amino/amide NH bonds (3310, 3188, 1534, and 736 cm −1 ) (Figure S5, Supporting Information) .…”
Section: Resultsmentioning
confidence: 99%
“…Although the role of FeCp 2 in carbon micro‐shell production is not certain, the origin of carbon micro‐shell might be the solvents used in their study. Our previous works have demonstrated that carbon materials (NPs, diamond‐like carbons) and their agglomerate are not formed from aliphatic hydrocarbons but from aromatic hydrocarbons by femtosecond NIR laser pulses . Aromatic solvent such as benzene and toluene may partially decompose to fragments that can form carbon nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…As for the productions of carbon NPs by femtosecond NIR laser pulses, the active species to form NPs is dependent on the reactants. For example, hydroxyl radicals act as oxidants when the benzene/water bilayer solution is used as a reactant,, whereas solvated electrons act as reductants when hexafluorobenzene or dichloromethane/water bilayer solution is used as a reactant . The production of precious metal NPs from aqueous solution by femtosecond NIR laser pulses is explained by the reduction of metal ions by hydrated electrons ,.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the chemistry beyond the primary reactions between DCM and e − aq is uncertain due to its complexity. It is noted that e − aq also attacks hexafluorobenzene dissolved in water to form CNPs [19]. 7, and H + (8) are 0.55×10 10 , 2.5×10 10 , 3.0×10 10 , 1.9×10 10 , and 2.3×10 10 dm 3 mol −1 s −1 , respectively [20].…”
Section: Discussionmentioning
confidence: 99%